Business Model Canvas : Brava / Muhamad Danial Hairudin - Hairudin, Muhamad Danial (2020)
The BMC report on my product which is BRAVA can act as the business plan. The goal is to look beyond spreadsheets, market research and financial projections. It is interesting to note that although the main focus of the BMC is to establish the foundation of the business model, it also may help in enhancing my business as it evolves. There are many advantages on BMC I can take for my new idea product which is, I have an overview of what my business model really is, I can also cut which activities are not so important. Moreover, by using BMC, I can clearly stack my idea into cleared structured form. In other words, it can offer me an overview of the business idea from every perspective, thus make it easier for my company executing the project of producing the product